SEBASTOPOLIS EXCAVATIONS AND OBSERVATIONS ON THE BYZANTINE CHURCH - Akın TEMÜR; İlknur GÜLTEKIN GENÇ (Journal of Ancient History and Archaeology)
The ancient city of Sebastopolis, located in Tokat's Sulusaray district, was unknown to researchers until the 19th century, when it came to earth in 1871 thanks to the finding of an inscription bearing the name of the city. In the process that started with the rescue excavations by the Tokat Museum in 1987, the city was excavated by different teams intermittently for 12 years. Although many finds were discovered during salvage excavations in the city, the excavations mostly focused on the “Roman Bath” and the “Byzantine Church”. Because the excavation sites are situated within current habitation areas and owing to complications regarding the expropriation of structures, the excavation process has advanced at a notably slow pace, necessitating intermittent interruptions in the excavations. The excavations conducted within the city's Byzantine Church have led to the conclusion that the structure follows a 'Domed Basilica Plan.' This architectural layout showcases features commonly observed in Early Period Byzantine Churches: three naves and three apses, all extending in the east-west direction. T The Sebastopolis Church is thought to have been built between the 7th and 9th centuries AD, based on the information collected and considering the architectural design, construction techniques, and materials of that time. Considering the large amount of Roman pottery unearthed during the excavations, the first phase of the structure can be dated back to earlier periods and it may have been built on a Roman structure. Accurate dating and a comprehensive understanding of its developmental stages will be achievable only after unearthing the narthex and atrium sections, if any, situated beneath the contemporary structures to the west of the church.